2007
DOI: 10.1007/s11832-007-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

Screw placement in slipped upper femoral epiphysis: Is good the enemy of better?

Abstract: Introduction and aims A single hip screw is the recommended method of fixation for slipped upper femoral epiphysis (SUFE). Current practice favours the placement of the screw in the centre of the femoral head on both anteroposterior and lateral planes to avoid the risks of chondrolysis and avascular necrosis (AVN). We investigated the correlation between different positions of the screw in the femoral head and the prevalence of AVN, chondrolysis, late slippage and the time to epiphyseal closure.Methods The cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Screw fixation seems to be associated with a lower complication rate [2,4,10,17,18]. Therefore, single-screw fixation is, at present, the most common [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Screw fixation seems to be associated with a lower complication rate [2,4,10,17,18]. Therefore, single-screw fixation is, at present, the most common [19].…”
Section: Discussionmentioning
confidence: 99%
“…The type of implant used to fix the epiphysis remains controversial. Screw fixation seems to be associated with a lower complication rate [2, 4, 10, 17, 18]. Therefore, single-screw fixation is, at present, the most common treatment for SCFE [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goals of screw fixation for the treatment of SCFE are stabilizing the physis, preventing further slippage, avoiding avascular necrosis or chondrolysis, and promoting physeal closure. A technique that utilizes a single hip screw has shown to provide a good outcome in the short and intermediate term [26,30]. A study by Jamil et al [30] showed that screw positioning other than in the center of the femoral head can also provide physeal stability and has no correlation with the timing of epiphyseal closure and the risks of avascular necrosis and chondrolysis in mild cases.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding screw tip position in the epiphysis, Jamil compared the center-center position with placements outside of this location 20. They found no late slippage or chondrolysis in either group and screw position did not influence time to physeal closure, concluding that positions outside of the “ideal” center-center location are adequate to provide physeal stability.…”
Section: Discussionmentioning
confidence: 99%